Therapeutic Targets in Chlamydial Fatty Acid and Phospholipid Synthesis - Yao, Jiangwei; Rock, Charles O. (Frontiers in Microbiology, 2018)
Chlamydia trachomatis is an obligate intracellular pathogen with a reduced genome reflecting its host cell dependent life style. However, C. trachomatis has retained all of the genes required for fatty acid and phospholipid synthesis that are present in free-living bacteria. C. trachomatis assembles its cellular membrane using its own biosynthetic machinery utilizing glucose, isoleucine, and serine. This pathway produces disaturated phospholipid molecular species containing a branched-chain 15-carbon fatty acid in the 2-position, which are distinct from the structures of host phospholipids. The enoyl reductase step (FabI) is a target for antimicrobial drug discovery, and the developmental candidate, AFN-1252, blocks the activity of CtFabI. The x-ray crystal structure of the CtFabI•NADH•AFN-1252 ternary complex reveals the interactions between the drug, protein, and cofactor. AFN-1252 treatment of C. trachomatis-infected HeLa cells at any point in the infection cycle reduces infectious titers, and treatment at the time of infection prevents the first cell division. Fatty acid synthesis is essential for C. trachomatis proliferation within its eukaryotic host, and CtFabI is a validated therapeutic target against C. trachomatis.